CORRELATION OF LOW BACK PAIN WITH BODY MASS INDEX, FUNCTIONAL REACH TEST AMONG FEMALE NURSING PROFESSIONALS (International Journal of Physiotherapy, 2015)
Background: Among health care workers the highest level of work related back injuries are more affected in nurses. There were many studies done to assess low back pain by using different tools. So this study aimed to identify the prevalence low back pain disability among female nursing professionals and the association between BMI, functional reach test and low back pain, so that a better tool can be used during the clinical examination for the betterment of the patient. The objective of the study is to identify the prevalence of low back pain disability, the association of Low Back Pain(LBP) with BMI and functional reach test among female nursing professionals.Methods: A total of 256 subjects were assessed for disability due to back pain using OswestryLBP Disability Questionnaire and the prevalence of disability was determined. The sit and reach test, forward reach test and their BMI were calculated for those who had a disability score of 20 and above (n=87).Results: Data was analyzed using Pearson’s correlation.The study result showed a significant correlation (p=0.03) of sit and reach test with low back pain disability scores. There was a negative correlationseen among BMI and LBP disability score forward reach test and LBP disability score, and BMI and no low back pain disability score.Conclusion: The prevalence of LBP disability among nursing professionals was 33.9%. This study suggest that sit and reach test can be used as an indicator of low back pain. Whereas BMI and forward reach test do not indicate low back pain.